1996
DOI: 10.1002/mrm.1910360610
|View full text |Cite
|
Sign up to set email alerts
|

Lactate, N‐acetylaspartate, choline and creatine concentrations, and spin‐spin relaxation in thalamic and occipito‐parietal regions of developing human brain

Abstract: Previous studies of the brains of normal infants demonstrated lower lactate (Lac)/choline (Cho), Lac/creatine (Cr), and Lac/ N-acetylaspartate (Naa) peak-area ratios in the thalamic region (predominantly gray matter) compared with occipitoparietal (mainly unmyelinated white matter) values. In the present study, thalamic Cho, Cr, and Naa concentrations between 32-42 weeks' gestational plus postnatal age were greater than occipito-parietal: 4.6 +/- 0.8 (mean +/- SE), 10.5 +/- 2.0, and 9.0 +/- 0.7 versus 1.8 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
68
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 62 publications
10
68
5
Order By: Relevance
“…They suggested that Lac might be produced locally or in peripheral tissues and that it may play a role in brain metabolism. Cady et al (37) found a decreasing Lac concentration with increasing gestational age in the thalamus and occipital-parietal region, indicating a changing glycolytic activity in the immature brain of AGA infants. Lac may be used as fuel for the brain but also for the synthesis of myelin (38).…”
Section: Discussionmentioning
confidence: 97%
“…They suggested that Lac might be produced locally or in peripheral tissues and that it may play a role in brain metabolism. Cady et al (37) found a decreasing Lac concentration with increasing gestational age in the thalamus and occipital-parietal region, indicating a changing glycolytic activity in the immature brain of AGA infants. Lac may be used as fuel for the brain but also for the synthesis of myelin (38).…”
Section: Discussionmentioning
confidence: 97%
“…33 Interestingly, a developmental increase in T2 values of metabolites has been found in the mouse developing brain, 34 and in the human brain (NAA and Cho) from 32 to 42 weeks postconceptional age. 16 So far, small pools of bound creatine 35 or lactate 36 have been detected in the adult brain but have not been investigated in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol of spectroscopy included 1 H-MR spectroscopy performed at short and long TE, because long TEs allow unambiguous detection of lactate signal owing to lipid signal suppression, which may be important in the context of prematurity. 16 A better understanding of how normal cerebral maturation in fetuses and premature neonates evolves is essential for the early detection of pathologic alterations and the assessment of therapeutic interventions. The second aim of this study was to assess whether cerebral microstructural and metabolic data obtained from premature neonates by using MR imaging and MR spectroscopy techniques might help evaluate normal brain maturation in utero.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Elevated brain metabolite ratios, lactate/Nacetylaspartate (NAA) and lactate/choline, have been associated with poor neurodevelopmental status in neonates with hypoxic-ischemic encephalopathy. 1,10,12,13 The increase in brain lactate level is thought to be a result of anaerobic rather than oxidative energy metabolism during cellular hypoxia.…”
mentioning
confidence: 99%